(untitled) (Global Scientific Review, 2023)
In this case, the boxer will focus his attention on the preparatory stage of the start of the movement. In this case, the motor centers of the cerebral cortex are excited and are in the starting state. Excitation reaches the motor area of the cerebral cortex and meets there already prepared nervous formulas of response movement, and the corresponding motor impulses instantly rush to the organs of movement.